Development of modern physics practicum e-guide on circular iris difraction materials to calculate He-Ne laser wavelength using professional flip pdf application - Sitinjak, Hardiantinus; Purwaningsih, Sri; Falah, Hebat Shidow (Universitas Muhammadiyah Mataram, 2024)
Development of a modern physics practicum guide on circular iris diffraction material to calculate the He-Ne laser wavelength using the Flip PDF Professional application. To determine student perceptions, as well as the feasibility of developing a modern physics practicum guide on circular iris diffraction material to calculate the He-Ne laser wavelength using the Flip PDF Professional application. This research was carried out using research and development (R&D) methods. R&D is a research method used to produce certain products, and test the effectiveness of these products. In this research, the product produced is a practical guide on circular iris diffraction material using a He-Ne laser, to calculate wavelengths which are expected to increase interest in learning and understanding of modern physics concepts for students. The result of this development is an e-guide to modern physics practicum on circular iris diffraction material to calculate He-Ne laser wavelengths using the Flip PDF Professional application.This electronic practicum e-guide was developed using the 4 (D) model which consists of 4 stages, namely the define stage, design stage, develop stage and disseminate stage. The development of a modern physics e-guide using Flip PDF Professional on material measuring He-Ne laser wavelengths with a circular iris diffraction pattern was carried out to assist students in understanding the learning material so that they were able to understand the practical material on measuring He-Ne laser wavelengths with a circular iris diffraction pattern Before the e-guide was developed, a preliminary study was carried out to determine the basis for developing the e-guide for modern physics. For student responses, the average score was 3.86 and a percentage of 96% was in the very good category. The media validation results got an average of 3.13 in the very good category, for material expert validation they got a very good category with an average of 4. So the guide created in the category is suitable for use.